2017
DOI: 10.1073/pnas.1707778114
|View full text |Cite
|
Sign up to set email alerts
|

Confined in-fiber solidification and structural control of silicon and silicon−germanium microparticles

Abstract: Crystallization of microdroplets of molten alloys could, in principle, present a number of possible morphological outcomes, depending on the symmetry of the propagating solidification front and its velocity, such as axial or spherically symmetric species segregation. However, because of thermal or constitutional supercooling, resulting droplets often only display dendritic morphologies. Here we report on the crystallization of alloyed droplets of controlled micrometer dimensions comprising silicon and germaniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 44 publications
3
60
0
Order By: Relevance
“…Fabrication of in‐fiber particles has been achieved by softening the prefabricated fibers either by isothermal heating via furnace or by axial thermal‐gradient heating via oxyhydrogen flame or furnace . However, these approaches face some challenges, such as wide and uncontrollable heating profiles, unavoidable satellite particle generation, and a limited selection of functional materials, all of which have limited their study and possible applications.…”
Section: The Fluid Dynamics and Rheology Of Thermal Drawingmentioning
confidence: 99%
See 1 more Smart Citation
“…Fabrication of in‐fiber particles has been achieved by softening the prefabricated fibers either by isothermal heating via furnace or by axial thermal‐gradient heating via oxyhydrogen flame or furnace . However, these approaches face some challenges, such as wide and uncontrollable heating profiles, unavoidable satellite particle generation, and a limited selection of functional materials, all of which have limited their study and possible applications.…”
Section: The Fluid Dynamics and Rheology Of Thermal Drawingmentioning
confidence: 99%
“…The versatility of the laser‐based solidification approach has also been demonstrated for tailoring the microstructure of in‐fiber SiGe spheres obtained via PRI. By precisely controlling the heating and cooling rates, Gumennik et al showed the creation of SiGe compositionally segregated Janus spheres and spheres of dendrites of Ge in Si in silica fibers . Another appealing example is to modify the electronic band structure of in‐fiber semiconductors via the high stress introduced during the laser solidification process.…”
Section: Microstructure Engineering Of Functional Materialsmentioning
confidence: 99%
“…Even further complexity in digital preform design was highlighted for solely or combined radial and azimuthal control on particles [31]. In addition, control on solidification front and recrystallization, microstructure and stress control on SiGe alloy spheres was demonstrated for bandgap modification and in-fiber microelectronics [34].…”
Section: Digital Design Of Particle Structuresmentioning
confidence: 99%
“…The literature on Group IV semiconductor-core glass fibers is now significant [1][2][3][4][5], including processing improvements [6][7][8] and device demonstrations [9][10][11][12][13][14][15][16][17]. There are also reports on both SiGe alloy and II-VI core fibers [18][19][20][21][22][23], one including low temperature photoluminescence [21]. However, there is limited information on III-V semiconductor-core fibers [26][27][28] manufactured by either CVD or molten-core techniques.…”
Section: Introductionmentioning
confidence: 99%